Students' Entrepreneurial Interests Reviewed From Economic Literacy With Motivation As An Intervening Variable (Case Study Of Feb Students Of Harapan University Medan - Rizky Daulay, Alfina; Muhar, Ani Murwani; Sari, Ade Indah (Cattleya Darmaya Fortuna, 2025)
This study aims to determine the effect of economic literacy on entrepreneurial motivation. To determine the effect of economic literacy and entrepreneurial motivation on students' entrepreneurial interest partially. To determine the effect of economic literacy on students' entrepreneurial interest through entrepreneurial motivation in FEB students of Harapan University Medan. The population in this study was 338 FEB students of Harapan University Medan and using the Arikunto formula of 30%, a sample of 198 people was obtained. The results of the study indicate that economic literacy has a positive and significant effect on students' interest in entrepreneurship, entrepreneurial motivation has a positive and significant effect on students' interest in entrepreneurship, economic literacy has a positive and significant effect on entrepreneurial motivation, entrepreneurial motivation does not mediate the effect of economic literacy on students' interest in entrepreneurship.